CPIA Africa, June 2014 : Assessing Africa's Policies and Institutions - World Bank Group (Washington, DC, 2014)
This report describes the progress African countries are making on strengthening the quality of policies and institutions that underpin development. It presents Country Policy and Institutional Assessment (CPIA) scores for the 39 African countries that are eligible for support from the International Development Association (IDA). This year's report expands coverage to include Djibouti and Yemen from the Middle East and North Africa region (MENA). The scores, which are on a scale of 1 to 6 with 6 being the highest, are an indicator of the quality of these countries' policy and institutional framework across 16 dimensions grouped into four clusters: economic management (Cluster A), structural policies (Cluster B), policies for social inclusion and equity (Cluster C), and public sector management and institutions (Cluster D). The overall quality of policies and institutions in Sub-Saharan African countries held steady in 2013, with divergent performance across countries. The average CPIA score for Sub-Saharan Africa held steady at 3.2 in 2013. But beyond the flat regional average, there was considerable divergence in country performance. For the region's IDA borrowers, scores were in a range of 3.9 to 2.0. A broad-based deepening of policy reforms lifted Rwanda's CPIA score in 2013, and the country joined Cabo Verde and Kenya at the top of the score range. Other top performers include Burkina Faso, Senegal, and Tanzania (all with scores of 3.8). South Sudan and Eritrea remained at the low-end of the score range (2.1 and 2,0, respectively), weighed down by deep policy and governance challenges. The quality of policies and institutions in MENA countries lags behind the average for middle income countries in all CPIA categories with scores lower relative to the Sub-Saharan African IDA country average. Since 2005, neither Yemen nor Djibouti has improved its overall rating; indeed, Yemen's overall policy and institutional score actually declined. The average CPIA score for countries in MENA was 3.0 in 2013, unchanged from 2012. Both Djibouti and Yemen had unchanged scores, indicating that despite unsettled conditions in the region and lingering challenges in global economic conditions, these countries generally opted to maintain their existing policy framework. Djibouti's CPIA score (3.1) was slightly higher than the average while Yemen's was on par with the average.